The Rain Gods' Rebellion : The Cultural Basis of a Nahua Insurgency - Taggart, James M., 1941- (Book collections on Project MUSE., 2020)
"Examines Nahua oral narratives to illuminate the cultural basis of the 1977-1984 rebellion against Hispanic elite in Huitzilan de SerdaÌn, Mexico. Forty years of fieldwork traces the sociopolitical role of rain gods-human and divine forms-hundreds of years explaining connections between social experiences and water/weather"--